Flavin Conjugated Polydopamine Nanoparticles Displaying Light-Driven Monooxygenase Activity - Crocker, Leander; Fruk, Ljiljana (Frontiers in Chemistry, 2019)
A hybrid of flavin and polydopamine (PDA) is explored as a photocatalyst drawing inspiration from natural flavoenzymes. Light-driven monoxygenase activity is demonstrated through oxidation of indole under blue light irradiation in ambient conditions to afford indigo and indirubin dyes. Compared to the free flavin, flavin-polydopamine hybrid is shown to be more resistant to photobleaching and more selective towards dye production. In addition it was demonstrated that it can be recycled from the solution and used up to 4 cycles without the marked loss of activity, which is a significant improvement to other heterogenous flavin catalysts. Mechanism of action was explored indicating that PDA shell plays and important role in stabilisation of the intermediate flavin-peroxy species, being an active component of the catalytic system rather than acting only as a passive nanocarrier of active centres.